Manake Media Equipment Rental System with Payment Gateway and Business Process Optimization - Fikri Mulya Rachmat; Cholid Mawardi; Yudha Pradana (Institut Teknologi Bisnis AAS Indonesia, 2026)
Media equipment rentals are time-sensitive because a single item can only be booked within a specific date range and requires payment confirmation before the unit is prepared. Manual handling through WhatsApp conversations and bank transfers often creates obstacles such as slow confirmation, schedule conflicts, and non-standardized transaction records. This study designs and implements “Manake”, a web-based media equipment rental management system that integrates the Midtrans payment gateway (Snap) and webhooks to synchronize payment status in real time. Development follows the Waterfall model, covering requirements analysis, design, implementation, and testing. The system is built using Laravel 12 (PHP 8.5.2), a Tailwind CSS interface through Vite, and a managed PostgreSQL database on Supabase. Business rules are embedded directly into the system, including a one-day operational buffer before and after the rental period, a reschedule policy limited to one time before pickup with no refunds, percentage-based late-return penalties calculated per order, and minimum damage fees calculated per item. Evaluation is conducted using black-box testing on core scenarios aligned with the business flow (catalog, cart, checkout, payment, invoice, and admin operations). The results show that all main functions run according to specification, and the webhook integration is able to update transaction status automatically through signature validation and event deduplication mechanisms.